PENGARUH SISTEM INFORMASI AKUNTANSI, SISTEM PENGENDALIAN INTERNAL DAN KINERJA PEGAWAI TERHADAP KARAKTERISTIK LAPORAN KEUANGAN: THE EFFECT OF ACCOUNTING INFORMATION SYSTEM, INTERNAL CONTROL SYSTEM AND EMPLOYEE PERFORMANCE ON THE CHARACTERISTICS OF FINANCIAL STATEMENTS - Halimatus Sakdiah; Netty Herawaty; Fredy Olimsar (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2023)
The goal of this study is to determine and evaluate the influence of accounting information system, internal control system and employee performance on the characteristics of financial statements at the Public Works and Public Housing Office of Jambi Province. This study utilized both primary and secondary data on a sample of 50 employees involved in the financial process of the Jambi Provincial Public Works and Public Housing Service. Data collection using the questionnaire method using an interval scale. Analyses of multiple linear regression by using SPSS for Windows. The findings revealed that partially and simultaneously the variables of the accounting information system, internal control system and employee performance affect the characteristics of financial statements at the Public Works and Public Housing Office of Jambi Province.